POPULATION CONDITIONS OF ECHINOIDEA AND CORAL REEF COVERS IN PONCAN GODANG ISLAND, SIBOLGA, NORTH SUMATERA - Adni, Nailul; Mulyadi, Aras; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2021)
Poncan Godang Island is included in the appropriate category based on the suitability of land for the Sibolga tourist area, with the presence of tourism activities that can also affect the amount of biodiversity in it. Considering the importance of coral reefs for biodiversity and sea urchins which also have a role in coral reef ecosystems, it is necessary to conduct research on the condition of sea urchins population and the percentage of coral reefs on Poncan Godang Island. Sea urchin and coral reef data were collected using the Line Intercept Transect (LIT) method by monitoring directly on the transect line along 50 meters. The results obtained indicate that the population of sea urchins in the waters of Poncan Godang Island, North Sumatra can be described, that sea urchins do not affect the coral reef ecosystem because at stations 1 and 5 there is no sea urchin and the percentage of coral cover is classified as bad, but at station 3 there are 32 individuals with coral reef cover conditions, while at stations with The percentage of good coral cover is that at station 4 there are only 25 individuals, as well as at station 2 where the percentage of coral cover is higher than station 3 and there are no sea urchins.